Changes in Jail Inmates' community connectedness across the period of incarceration. Issue 8 (3rd August 2019) - Folk, Johanna B.; Mashek, Debra J.; Stuewig, Jeffrey B.; Tangney, June P.; Moore, Kelly E.; Blasko, Brandy L.
ABSTRACT: Jails bring inmates into proximity with one another and separate them from the community. Because inmates' connectedness to one another and to the community influences post-release functioning, understanding risk factors for maladaptive shifts in connectedness may inform interventions. The current study examined changes in jail inmates' ( N = 203) connectedness to the community at large and to the criminal community, and predictors of individual differences in changes over time. Connectedness to both communities did not change on average during incarceration, but younger and less guilt-prone inmates increased more in connectedness to the criminal community than older and more guilt-prone inmates, suggesting connectedness interventions should target individuals exhibiting this constellation of attributes.